The Significance and Impact of the Family Structure on the Proneness to Conflict of Preadolescent Students - Džaferović, Mirsada; Džaferović, Jasmin; Stojanović, Biljana (Technium Social Sciences Journal, 2022)
The aim of the paper was to examine the significance and impact of the family structure on the proneness to conflict of preadolescent students. The research involved 400 seventh grade students. At the very beginning of the presentation of the results, the proneness to conflict of preadolescent students was established. By applying the x2testfor one variable, it has been determined that the highest number of students enter into conflicts one or two times per month (N = 205). The second place is occupied by a group of students who enter into conflicts one or two times per week (N = 91). In the second part of the analysis, the Mann-Whitney test was applied, whereby an independent variable (completeness of the family) was crossed with a dependent variable (related to the frequency of conflicts, ranging from 1-very rarely to 4-daily).A conclusion was reached that a significantly higher number of conflicts (Z = -2.18, p < .05) are initiated by children from incomplete families (Mrank = 218.51), ascompared to children from complete families (Mrank = 192.16).In the third part of the paper, Spearman’s correlation coefficient - rho (rs) was applied. A multiple regression analysis indicated that the educational level of the parents has a more significant impact on the proneness to conflict of students, i.e. that students who come from families where the parents have completed university education, master’s or doctoral studies, more rarely enter into conflicts, in comparison with students who come from families where the parents have completed college, secondary or primary education, namely, that the lower the educational level of the parents (father or mother), the greater the child’s proneness to conflicts. In order to examine the correlation between the sociodemographic characteristics of the family (education of the father, education of the mother and completeness of the family) and the child (sex and age),and the frequency of conflicts, a multiple regression analysis was applied. The predictor (independent) variables, presented as the sociodemographic characteristics of the family and the child, in relation to the criterion variable, which represents the frequency of conflicts, indicate the results of this analysis and point to the conclusion that the sociodemographic characteristics of the family and the child are significantly related to the outcomes of the conflicts (F(388, 5) = 2.74, p < .05; R = .185).